The conceptual quantitative assessment framework for Nature-based Solutions (NbS) - Sumonrat Chairat; Shabbir H. Gheewala (Nature-Based Solutions)
Nature-based solutions (NbS) are recognized as one of the approaches that can address a range of environmental issues, often with conservation and natural resource management missions. However, the promotion of NbS often lacks a robust understanding of their actual impacts and effectiveness. To support the evaluation and implementation of NbS, there is a need for a comprehensive quantitative assessment framework. The main objectives of the study are to (1) develop an assessment framework that can be used to quantify the performance of NbS interventions and to (2) provide a step-by-step guideline for evaluating NbS. The assessment framework proposed in this study was built upon existing frameworks used in previous studies, designed to address specific gaps. Several aspects and tools were integrated in response to the NbS standard criteria provided by the International Union for Conservation of Nature (IUCN), as a result, this quantitative assessment framework can provide a comprehensive evidence based on environmental, social, and economic aspects. The study introduced one approach, viz., the System of Environmental-Economic Accounting - Ecosystem Accounting (SEEA EA), and three main assessment tools (i.e., Life Cycle Assessment (LCA), Social Life Cycle Assessment (S-LCA), and Cost-Benefit Assessment (CBA)) aimed at facilitating a comprehensive evaluation of NbS. The results provide a conceptual framework that offers a systematic approach for evaluating the performance of NbS, along with methods to address conflicting results among aspects and/or indicators. Ideas and approaches for assessing ecosystem services provided by NbS and primary concerns when conducting NbS assessments are also highlighted. In summary, the conceptual framework proposed in this study can be used to assess NbS performance and determine whether NbS interventions align with the NbS standard criteria provided by IUCN, utilizing the introduced assessment tools.